Progression and management of Prediabetes by socioeconomic status and health care consumption. The Tromsø Study 2007-2016 - Yemane, Dagmawi (UiT Norges arktiske universitet, 2023)
Background: Socioeconomic status and healthcare consumption are considered predictors of diabetes development and quality of blood glucose management. However, studies on the association between socioeconomic status and healthcare consumption in people with prediabetes and these outcomes are scarce. Objective: To examine the relationship between the development of diabetes in people with prediabetes and socioeconomic status as well as healthcare consumption. Furthermore, blood glucose management in people with prediabetes is also examined as diabetic complications usually occur before the diagnosis of diabetes and can be prevented by screening and early management. Methods: I used a cohort study using data from two waves of the population-based Tromsø Study utilizing socioeconomic variables, anthropometric variables, healthcare consumption, exercise, and smoking information collected from the questionnaire, and HbA1c data collected from laboratory data along with demographic and information on personal and family history of diabetes. These variables are analyzed using binary logistic regression analysis, linear regression analysis, and mediation analysis. Main results: From the 2690 participants with prediabetes included in wave 6 of the Tromsø Study, 304 representing 11.3% of participants had developed diabetes at follow up 7-8 years later (wave 7 of the Tromsø Study). Those with an upper secondary level of education had 54% higher odds of a diagnosis of diabetes relative to those with four or more years of college/university level of education. While there was a 0.06-unit change in HbA1c levels in participants with the lowest levels of education compared to those with the highest. Furthermore, those with 5 or more GP visits over the 12 months prior to Tromsø 6 had 74% higher odds of getting diagnosed with diabetes than those with 1 visit. Conclusions: While the association of healthcare consumption on the progression of the disease in the study participants is not established, there is a socioeconomic ...